Video Atlas of Arthroscopic Rotator Cuff Repair - Srikumaran, Uma (Thieme Medical Publishers, Incorporated, 2020)
Fundamentals in rotator cuff repair and reconstruction from world-renowned experts! Rotator cuff disorders are the most common cause of shoulder pain, accounting for up to 70% of cases. Tears are the most severe subtype, with a lifetime prevalence rate of more than 20%. The size, location, and severity of rotator cuff tears varies greatly, requiring equally diverse preoperative planning and surgical interventions. Video Atlas of Arthroscopic Rotator Cuff Repair by Uma Srikumaran and esteemed contributors provides a concise, well-rounded perspective on the surgical management of rotator cuff pa.